Analisis Upaya Pencegahan Anemia Ibu Hamil Pada Masa Pandemi COVID-19 - Mera Marhamah; Anes Patria Kumala (NHM PRESS, 2022)
Anemia during pregnancy is associated with maternal morbidity and an indirect cause of maternal mortality in the entire population of pregnant women. In this Covid-19 pandemic situation, there are many restrictions to almost all public services including maternal and neonatal health services, thereby increasing the risk of an increase in anemia among pregnant women. The aims of study to determine the prevention of anemia for pregnant women during the Covid-19 pandemic at midwife’s private practice in susukan sub-district area, east jakarta. The design of this research is a quantitative analytic study with a cross sectional approach. Samples were 100 pregnant women. Sampling used Accidental Sampling technique. The instrument used was a valid and reliable questionnaire. Data were analyzed using Chi square test. Out of 100 pregnant women, 57% had good anemia prevention efforts during the COVID-19 pandemic, 58% lacked diet, 57% lacked family support and 77% of pregnant women were less obedient to taking tablets Fe. The results of the Chi square test showed that there was a significant relationship between diet, family support, compliance with Fe tablet consumption with efforts to prevent anemia of pregnant women during the Covid-19 pandemic. The factor that most influences the prevention of anemia during the Covid-19 pandemic is family support (OR = 4,538).